Signs of change An artist's book utilizing the diaristic approach in revealing local sign lettering in Quezin City and Manila - its value and decline as a skill and craft - Canay, Isias Domingo Emmanuel L. (2013)
Sign lettering plays a role in shaping our commercial landscape and community in the field of visual arts and advertising. Yet it is also one of the least studied, recognized and appreciated forms of craft in the Philippines. In Quezon City and Manila, sign lettering practitioners - sign painters - are seen struggling with their profession because it could no longer support their everyday needs. Local sign lettering are now being replaced by digital letterings and printing made by computers. The newer technology made labor easier ant the public is ready to leave the traditional skill behind. At this point, only few people are aware of and are interested in it. Because of the dismal state and future of local sign lettering in the two cities, it may disappear. This study aimed to effectively raise public interest, appreciation and awareness of local sign lettering as a trade and means of livelihood through the publication of a book. To attain this, the researcher suggested the use of the diaristic approach and tested it to know if it helped achieve the aims of the study. From the gathered data and analysis, results showed that the diaristic approach was effective as a means to inform the public of the craft and ignite interest. The book, which followed the research, showed the existing condition of sign lettering in Quezon City and Manila. In the book, readers followed the lives and plights of 4 sign painters, kuya Ely, store lettering, kuya Bob, tricycle lettering, kuya Sonny, taxi lettering and, kuya Bobby, signboard lettering. By reading first-hand accounts of these sign painters, readers gained understanding of their circumstances.